P275 HOLDING AREA IN EMERGENCY DEPARTMENT : A STRATEGY TO IMPROVE ADHERENCE TO INTERNATIONAL GUIDELINES IN CASES OF PULMONARY EMBOLISM IN ELDERLY. (18th May 2022) - Savioli, G; Ceresa, I; Mugellini, A; Martignoni, A; Fumoso, F; Lapia, F; Brattoli, M; Maggioni, P; Preda, L; Lava, M; Muzzi, A; Novelli, V; et al.
Abstract: Premises: Pulmonary embolism is a disease still characterized by high mortality. Despite a great development of the guidelines it is not clear what adherence to them is in real life, especially in the emergency room. Purpose of the Study: See if and how, in the real life of an Emergency Department, adherence to the Guidelines varies according to the area to which the patient is addressed. Methods: Monocentric retrospective observational study, on a group of geriatric patients (<75 y) that include all the people accessed to our ED, where they received acute PE dignosis. Enrolment started on 2016 and finished on 2019. We collected data from medical history, physical examination, lab tests, imaging; we calculated characteristic scores from the diagostic/therapeutic algorhitm, both regarding PE risk (Wells, Geneva and Years), and the 30–day mortality risk presentazione (sPESI). We then analized guidelines adherence in three decision–making turning–points: 1 Correct applicarion of decisional scores examined, which classify the patient in low, intermediate or high risk of PE, calculated with Wells and simplified Geneva score; 2 Correct therapy administration since the ED as suggested by the guidelines; 3 The eventual observation in the medium–intensity care area with close monitoring for the subpopulation of patients with finding of right ventricular dilation or myocardial enzymes impairement (considered at high risk of short–term shock and mortality). Results: we enrolled 249 patients, with a mean age of 83 years and female prevalence (F = 62%). Of these, 69% were referred by Triage to medium–high intensity of care, the remaining 31% was directed to low intensity of care. 42.5% of the total patients were referred to OBI. The two areas of intensity of care showed similar adherence to guidelines (approximately 50%) without there being a statistically significant difference between the two areas (p > 0.05) Adherence to guidelines was higher in the holding area – OBI (75 %) compared to that of those managed in theaters (50%) in a statistically significant way (p < 0.001). Conclusions: The study suggests that holding areas located in Emergency Departments can considerably increase adherence to international guidelines.